Cortical Modulation After Two Different Repetitive Transcranial Magnetic Stimulation Protocols in Similar Ischemic Stroke Patients - Hanafi, Muhammad Hafiz; Kassim, Nur Karyatee; Ibrahim, Al Hafiz; Mohd Adnan, Munirah; Ahmad, Wan Muhamad Amir Wan; Idris, Zamzuri; Abdul Latif, Lydia (Penerbit Universiti Sains Malaysia, 2018)
Background: Stroke is one of the leading causes of mortality and morbidity in Malaysia. Repetitive transcranial magnetic stimulation (rTMS) is one of the new non-invasive modality to enhance the motor recovery in stroke patients. Objectives: This pilot study compared the motor evoked potential (MEP) changes using different settings of rTMS in the post-ischemic stroke patient. The goal of the study is to identify effect sizes for a further trial and evaluate safety aspects. Methods: Eight post-stroke patients with upper limb hemiparesis for at least six months duration were studied in a tertiary hospital in Northeast Malaysia. Quasi experimental design was applied and the participants were randomised into two groups using software generated random numbers. One of the two settings: i) inhibitory setting, or ii) facilitatory setting have been applied randomly during the first meeting. The motor evoked potential (MEP) were recorded before and after application of the rTMS setting. A week later, a similar procedure will be repeated but using different setting than the first intervention. Each patient will serve as their own control. Repeated measures ANOVA test was applied to determine the effect sizes for both intervention through the options of partial eta-squared (η 2 p). Result: The study observed large effect sizes (η 2 p > 0.14) for both rTMS settings in the lesion and non-lesion sides. For safety aspects, no minor or major side effects associated with the rTMS was reported by the participants. Conclusions: The partial eta square of MEP value for both rTMS settings (fascilitatory and inhibitory) in both lesion and non-lesion sides represents large effect sizes. We recommend further trial to increase number of sample in order to study the effectiveness of both settings in ischemic stroke patient. Our preliminary data showed both settings may improve the MEP of the upper extremity in the ischemic stroke patient. No significant improvement noted when comparing both settings.